MARKETING COMMODITY POLICY OF AGRICULTURAL ENTERPRISES ON THE MARKET OF SUNFLOWER (INNOVATIVE ECONOMY, 2020)
Kulish T.V. MARKETING COMMODITY POLICY OF AGRICULTURAL ENTERPRISES ON THE MARKET OF SUNFLOWERPurpose. The purpose of the study is to identify the main aspects formation of agricultural enterprises marketing policy, taking into account marketing environment factors.Methodology of research. To achieve this goal, the following tasks were set and solved in the work: determining the relevance of effective marketing commodity policy formation for agricultural enterprises; research of macro-marketing environment factors in the sunflower market; the evaluation influence of micro-marketing environment factors on the sunflower market; substantiation of alternatives for marketing commodity policy formation for agricultural enterprises in the sunflower market.Findings. As a result of the research, the macro and microenvironment factors of the sunflower seed market were analyzed, the opportunities and threats to the marketing environment were identified, and the main alternatives to the commodity policy formation for agricultural enterprises in the sunflower market were identified.Originality. To substantiate the marketing policy of agricultural enterprises, taking into account the marketing environment factors, we use an expert assessment of factors, the essence of which is to select factors, assess their impact, score and identify alternatives to realizing opportunities or overcoming threats. It is determined that in order to increase the efficiency of growing and selling sunflower seeds it is necessary: state regulation of export-import operations; the improvement regional placement of crops, the use of protection appropriate means, the strict adherence to the requirements of alternating sunflower crops in the fields of crop rotation, the introduction of high-yield hybrids, attracting the necessary funds for development of the industry and material resources.Practical value. As a result of the strengths and weaknesses analysis, the alternatives determined that the most appropriate for commodity policy formation of agricultural enterprises in the sunflower market is to expand the range of sunflower processing products and introduce organic production of sunflower seeds.Key words: marketing product policy; marketing environment; macro environment; microenvironment; alternatives.
Keywords: Key words; marketing product policy; marketing environment; macro environment; microenvironment; alternatives.